The Relationship of Myometrial Invasion Between Other Prognostic Parameters in Endometrial Cancer - Mehmet Sait Bakır; Ali Emre Tahaoğlu; Emre Erdoğdu; Cem Dane (Medical Network, 2017)
Objective: The aim of this study is to investigate the relationship between deep myometrial invasion and other prognostic factors in endometrial cancer. Recurrence rates, disease free survival and overall survival rates were evaluated in endometrial cancer patients with MI>50%. Sudy Design: A total of 132 patients with endometrial cancer who underwent surgical treatment between 2001 and 2011 were identified. Demographic, clinicopathological, surgical/adjuvant treatment and follow-up data were extracted. Results: Pelvic lymph node invasion ratio was 28,9% and para-aortic lymph node invasion ratio was 15,5% in patients with myometrial invasion is greater than 50%. Other prognostic factors especially lympho-vascular space invasion and pelvic/para-aortic lymph node metastasis were significantly higher when myometrial invasion is above 50% and also there was significant difference in recurrence rates, overall survival and disease free survival rates between patients with superficial and deep myometrial invasion (p<0.05). Conclusion: Myometrial invasion is an important prognostic parameter and can be determined intraoperatively to decide whether to perform pelvic and para-aortic lymph node dissection.